진행성 간세포암종의 새로운 면역 항암 치료 - 최현빈; Hyun Bin Choi; 유정주; Jeong-ju Yoo (The Korean journal of medicine, 2025)
With the advent of immunotherapy, the treatment paradigm for advanced hepatocellular carcinoma (HCC) has undergone a significant shift, surpassing that based on traditional first-line therapies such as sorafenib and lenvatinib. The findings of the IMbrave150 trial revealed that compared with sorafenib, the administration of atezolizumab plus bevacizumab can contribute to significant improvements in median overall survival (mOS) and progression-free survival. Similarly, the HIMALAYA trial revealed that compared with sorafenib, treatment with durvalumab plus tremelimumab achieved a superior mOS. On the basis of the findings of these pivotal phase III trials, both regimens have received approval from the Food and Drug Administration and the Korean Ministry of Food and Drug Safety as first-line therapies for the treatment of advanced HCC. Nevertheless, for patients who are ineligible for immunotherapy, sorafenib and lenvatinib, which were previously established as first-line therapies, remain viable options. Currently, however, there are no wellestablished second-line therapies for patients who progress having initially received first-line immunotherapy. In Korea, sorafenib and lenvatinib are permitted as second-line options subsequent to treatment with atezolizumab-bevacizumab, although their use is limited to non-reimbursed settings. Although the introduction of immunotherapy has revolutionized the therapeutic landscape for the treatment of advanced HCC, long-term data on safety and efficacy are essential, and there remains an urgent need for clinical studies for the development of effective second-line treatments. Addressing these issues will be essential for improving the outcome of patients with advanced HCC. (Korean J Med 2025;100:102-108)